Integrating the Seven Sappurisa Dhammas into the Ethical Standards of Thai Politicians in the Context of a Political Crisis of Public Trust: Integrating the Seven Sappurisa Dhammas into the Ethical Standards of Thai Politicians in the Context of a Political Crisis of Public Trust - Yamkosum , Jiratthachai; Phrakrukittiwarathorn; Yanamethi (Salangsing) , Phramaha Thainoi (RATANABUTH JOURNAL, 2026)
This academic article aims to examine the concept of the Seven Sappurisa Dhammas in Buddhism, explore the concept of the political crisis of public trust arising from the deterioration of ethical conduct in the exercise of political power, which has undermined the legitimacy of political institutions and the stability of Thailand’s democratic system, particularly over the past two decades. During this period, Thailand has experienced persistent political conflicts, military coups, corruption, and ethical controversies involving political office holders. The article further analyzes the compatibility between the Seven Sappurisa Dhammas and contemporary theories of political ethics and synthesizes a Buddhist ethical framework for politicians through the integration of the Seven Sappurisa Dhammas into the ethical standards of Thai politicians. The study employs documentary research and descriptive analysis. The findings reveal that the Seven Sappurisa Dhammas are highly compatible with the fundamental principles of contemporary political ethics, particularly the rule of law, accountability, transparency, commitment to the public interest, public participation, and ethical leadership. Their distinctive contribution lies in cultivating the internal moral character and ethical consciousness of political leaders, thereby reinforcing governance mechanisms based on the principles of good governance, promoting ethical exercise of political power, and enhancing the ethical standards expected of political leaders in society. Furthermore, this article proposes a Seven-Dimensional Buddhist Ethical Standards Framework for Politicians, synthesized through the integration of the Seven Sappurisa Dhammas with the concepts of contemporary political ethics. The proposed framework serves as a conceptual model for strengthening the ethical standards of Thai politicians and provides practical guidance for promoting good governance, political legitimacy, and the long-term sustainability of democratic governance.